Unveiling The Linguistic Journey: Investigating Word Class Acquisition In 3-5 Year Old Children Through A Qualitative Approach - Iqbal, Muhammad; Auliana, Auliana; Dinda Sari, Dwhy; Rahman, Fadhlur; Haekal, Muhammad (Universitas Nahdlatul Ulama Surabaya, 2023)
Early childhood language development is a multifaceted and intricate process that includes the acquisitionof various linguistic components. However, occurrence of language delays or disorders among 3-5-years-old children is a significant challenge that can impede this progression. These delays or disorders can have asignificant impact on word class acquisition, which is a fundamental aspect of language development. Thisstudy aims to elucidate the diverse types of word classes observed in the language acquisition process ofchildren aged 3-5 years in North Aceh. Specifically, the investigation focuses on noun, verb, and adjectiveword classes. Employing a qualitative approach within a descriptive research framework. Thus, variousdata collection techniques including observation, listening, recording, note-taking, and documentation,were utilized in this study. Purposive sampling was employed, resulting in a sample size of 5 participants.These five participants were selected based on their age criteria, research site location, language proficiency,active engagement in interactions, as well as their availability and willingness to participate. The primarydata source encompassed children aged 3-5 years, with a particular emphasis on nouns, verbs, and adjectivesderived from conversational interactions. The results revealed three distinct types of word classes in thelanguage acquisition process of children aged 3-5 years. Firstly, the noun word class encompassed a rangeof entities, such as people, animals, fruits, flowers, food and drinks, tableware, sports equipment, clothing,plants, transportation equipment, and other nouns typically associated with the child’s environment.Secondly, the verb word class comprised verbs accompanied by objects and verbs without objects. Thirdly,the adjective word class characterized the state of nouns or objects, encompassing descriptors relatedto mental attitude, shape, size, color, mileage, temperature and humidity, power of energy, and senseimpressions. This study sheds light on the diverse nature of language learning in children aged 3-5 yearsby evaluating and analyzing these distinct word classes. Equally significant, by examining the linguisticpatterns and structures that emerged during this time period, this study contributes to our understanding of how children acquire language during the preschool years.